Teaching Indonesian to Japanese Learners Using Yuki-Onna: Japanese Horror Stories for BIPA - Yudono, Kristophorus Divinanto Adi; Yulina, Christina Atika (Journal of Instructional and Development Researches, 2025)
This study aims to investigate the use of Japanese horror literature-specifically the Yuki-Onna narrative-as instructional material for teaching Indonesian as a Foreign Language (BIPA) to Japanese learners. The study focuses on exploring how culturally familiar horror stories support linguistic development, narrative competence, and intercultural understanding. A qualitative case study design was employed to examine the learning process and outcomes experienced by Japanese learners engaging with Yuki-Onna–based instructional activities. Data were collected from December 2024 to February 2025 through participant observation, open-ended interviews, and documentation analysis. The study involved two intermediate-level Japanese learners as participants. Instruments included observation field notes, interview guides, learning worksheets, and student-produced narratives. The collected data were analyzed using thematic analysis to identify patterns related to vocabulary acquisition, grammatical development, oral proficiency, creative expression, and intercultural awareness. Findings indicate that the use of Yuki-Onna stories enhanced learners’ vocabulary comprehension, grammatical accuracy, pronunciation, and narrative production. Learners demonstrated increased motivation, engagement, and reflective thinking when interacting with culturally resonant horror materials. The integration of multimodal elements-visual and auditory resources-further strengthened interpretive and creative skills. Additionally, cross-cultural comparisons with Indonesian folklore, such as Kuntilanak, facilitated deeper intercultural competence. The study suggests that literature-based and culturally responsive materials, particularly horror narratives from learners’ own cultures, hold strong pedagogical potential in BIPA instruction. Future research should involve larger and more diverse participant groups, explore additional genres or folklore traditions, and examine long-term impacts on intercultural literacy and language acquisition.